Interconnections between Minister Cabinets in Greece. A Bicentennial Study with Implications on Economy - Dimitrios Kydros; Persefoni Polychronidou (Scientific Annals of Economics and Business)
In this paper we deal with a network analysis of interconnected cabinets in Greece for an extended time period. In parallel, we present a small review of the economic crises that have occurred in Greece over this period. More particularly, we used historical sources to locate all different Greek governments and all economic crises starting from the 1821 Greek revolution to the present days. We also formed a two-mode (also known as affiliation) network of ministers and cabinets and subsequently created a network of interconnected cabinets. We used dedicated software to visualize this network and used Social Network Analytical procedures in order to calculate its properties. Finally, in an attempt to investigate possible relations between network metrics and economic crises, we note and discuss an interesting observation between a specific metrics and such major economic events. In our paper, we firstly introduce the context and present our research questions. We then present the relevant literature, mainly discussing the extent to which Social Network Analysis has been used to investigate patterns of behaviors in politics. We then proceed to presenting and applying our methodology on network creation, visualization and metrics computations. The following section discusses the longitudinal evolution of our network and the relation between its clustering coefficient and the emergence of economic crises. We then finalize our paper with some conclusions.